1985
DOI: 10.1152/ajpheart.1985.248.6.h883
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular failure induced by myocardial infarction. II. Tissue morphometry

Abstract: Three days after myocardial infarction involving 57% of the left ventricle in rats, the viable tissue of the left ventricle expanded 29%, whereas myocardial hypertrophy in the right ventricle was 19%. To determine whether tissue oxygenation in the hypertrophied ventricles was supported by a proportional growth of the capillary network, morphometric analysis was used to measure capillary luminal volume and surface densities and the diffusion distance for O2. The volume fraction of capillary lumen and the lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In particular, myocardial ischemia is characterized by a two-fold increase in alpha-l adrenoreceptor number (29) which contributes to the occurrence of malignant ventricular arrhythmias (30). Although a reduction in the oxygenation potential of the surviving myocardium early after infarction has been claimed at the level of the capillary microvasculature (3,6), measurements of coronary blood flow distribution have failed to demonstrate abnormalities in coronary perfusion consistent with myocardial ischemia (31). Moreover, the alterations in alpha-l adrenergic receptor number in congestive dilated cardiomyopathy in humans (28) occur over a period of many years of decompensated overload, whereas in the current experiments in rats, alpha-1 adrenoreceptor density was determined 1 wk after coronary occlusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, myocardial ischemia is characterized by a two-fold increase in alpha-l adrenoreceptor number (29) which contributes to the occurrence of malignant ventricular arrhythmias (30). Although a reduction in the oxygenation potential of the surviving myocardium early after infarction has been claimed at the level of the capillary microvasculature (3,6), measurements of coronary blood flow distribution have failed to demonstrate abnormalities in coronary perfusion consistent with myocardial ischemia (31). Moreover, the alterations in alpha-l adrenergic receptor number in congestive dilated cardiomyopathy in humans (28) occur over a period of many years of decompensated overload, whereas in the current experiments in rats, alpha-1 adrenoreceptor density was determined 1 wk after coronary occlusion.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, however, the signal that induces cellular growth is the critical factor for short and long term survival. Myocyte hypertrophy after infarction is an early event (1,3,6) that progresses with time (2) in an attempt to restore ventricular mass and improve function (1,3,6). Moreover, this growth adaptation involves augmentations in myocyte length which exceed those in cell diameter (1)(2)(3), implying that the altered hemodynamic state after infarction affects the preload more than the afterload (3).…”
Section: Introductionmentioning
confidence: 99%
“…No CD13 upregulation was observed in non risk areas, in accordance with earlier findings that adaptation of capillary microstructure fails to occur in viable tissues after MI. 15 As a next step, we took advantage of optical sectioning, highresolution (0.5ϫ0.5ϫ1 m) and large penetration depth of TPLSM to obtain a more comprehensive picture of CD13 distribution on angiogenic and quiescent vessels in this model. 16 Indeed, TPLSM allowed us to generate 3D-images of the vasculature in the target areas (see supplemental data).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were made with regard to the development of noninfarcted myocardium mass (see Results). In the overall group and in the individual study groups, however, no relevant differences were found between captopril and fosinopril in their ability to influence myocardial growth and its trigger, namely systolic wall stress [37, 38]. …”
Section: Discussionmentioning
confidence: 99%